Extending cost-benefit analysis for the sustainability impact of inter-urban Intelligent Transport Systems - Kolosz, Ben; Grant-Muller, Susan (Environmental Impact Assessment Review, 2015)
The paper reports research involving three cost-benefit analyses performed on different ITS schemes (Active Traffic Management, Intelligent Speed Adaptation and the Automated Highway System) on one of the UK's busiest highways - the M42. The environmental scope of the assets involved is widened to take into account the possibility of new technology linked by ICT and located within multiple spatial regions. The areas focused on in the study were data centre energy emissions, the embedded emissions of the road-side infrastructure, vehicle tailpipe emissions, additional hardware required by the vehicles (if applicable) and safety, and all aspects of sustainability. Dual discounting is applied which aims to provide a separate discount rate for environmental elements. For ATM, despite the energy costs of the data centre, the initial implementation costs and mitigation costs of its embedded emissions, a high cost-benefit ratio of 5.89 is achieved, although the scheme becomes less effective later on its lifecycle due to rising costs of energy. ISA and AHS generate a negative result, mainly due to the cost of getting the vehicle on the road. In order to negate these costs, the pricing of the vehicle should be scaled depending upon the technology that is outfitted. Retrofitting on vehicles without the technology should be paid for by the driver. ATM will offset greenhouse gas emissions by 99kt of CO2 equivalency over a 25year lifespan. This reduction has taken into account the expected improvement in vehicle technology. AHS is anticipated to save 280kt of CO2 equivalency over 15years of operational usage. However, this offset is largely dependent on assumptions such as the level of market penetration.
Keywords: Intelligent Transport Systems; Transport appraisal; Cost–benefit analysis; Environmental impact assessment; Sustainability